Laparoscopic inguinal hernia repair: A comparison of transabdominal preperitoneal and total extraperitoneal techniques—Results of initial experiences - ERGENÇ, MUHAMMER (My University, 2023)
AIMS: This study aimed to analyze the results of transabdominal preperitoneal (TAPP) and total extraperitoneal (TEP) repairs performed by two authors and to compare two laparoscopic methods. MATERIALS AND METHODS: Patients who underwent inguinal hernia surgery in a secondarycare hospital between 2019 and 2022 were evaluated retrospectively. Demographics, hernia side and type, primary or recurrent hernia situation, size of hernia orifice, operation type, postoperative complications, duration of operation, length of hospital stay, recurrence, and follow-up time were examined. Perioperative outcomes were compared between the two groups. RESULTS: One hundred and eleven patients were analyzed. The mean age was 49.4±13 years, with a male/female ratio of 106/5. About 82% of hernias were unilateral, and 18% were bilateral. Sixtyfour TAPP and 47 TEP repairs were performed. Follow-up time (months, mean ± standard deviation) (range) was 14.2±10 (1–37). About 42.3% of the hernias were direct, 49.5% were indirect, and 8.1% were pantaloon hernias. The recurrence rate was 1.8%. The operation time was significantly lower in the TEP than in TAPP (64.4±23.5, 96.7±31.9, respectively, P < 0.001). TAPP was preferred in patients with larger hernia orifices (P = 0.01). The two groups had no significant difference regarding postoperative complications and recurrence rate. CONCLUSION: Our study did not detect any significant difference between TAPP and TEP repair regarding recurrence rate and postoperative complication. Laparoscopic inguinal hernia repair, which has advantages such as short hospital stay and less pain, can be safely performed in a secondarycare hospital.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); Inguinal hernia; laparoscopic surgery; TAPP; TEP